Evaluation of the GenoType MTBDRsl Version 2.0 Assay for Second-Line Drug Resistance Detection of Mycobacterium tuberculosis Isolates in South Africa - Gardee, Y. (J Clin Microbiol, 2017)
Early detection of resistance to second-line antituberculosis drugs is important for the management of multidrug-resistant tuberculosis (MDR-TB). The GenoType MTBDRsl version 2.0 (VER 2.0) line probe assay has been redesigned for molecular detection of resistance-conferring mutations of fluoroquinolones (FLQ) (gyrA and gyrB genes) and second-line injectable drugs (SLID) (rrs and eis genes). The study evaluated the diagnostic performance of the GenoType MTBDRsl VER 2.0 assay for the detection of second-line drug resistance compared with phenotypic drug susceptibility testing (DST), using the Bactec MGIT 960 system on Mycobacterium tuberculosis complex isolates from South Africa. A total of 268 repository isolates collected between 2012 and 2014, which were rifampin monoresistant or MDR based on DST, were selected. MTBDRsl VER 2.0 testing was performed on these isolates and the results analyzed. The MTBDRsl VER 2.0 sensitivity and specificity indices for culture isolates were the following: FLQ, 100% (95% confidence interval [CI] 95.8 to 100%) and 98.9% (95% CI, 96.1 to 99.9%); SLID, 89.2% (95% CI, 79.1 to 95.6%) and 98.5% (95% CI, 95.7 to 99.7%). The sensitivity and specificity observed for individual SLID were the following: amikacin, 93.8% (95% CI, 79.2 to 99.2%) and 98.5% (95% CI, 95.5 to 99.7%); kanamycin, 89.2% (95% CI, 79.1 to 95.6%) and 98.5% (95% CI, 95.5 to 99.7%); and capreomycin, 86.2% (95% CI, 68.3 to 96.1%) and 95.9% (95% CI, 92.2 to 98.2%). An interoperator reproducibility of 100% and an overall interlaboratory performance of 93% to 96% were found. The overall improvement in sensitivity and specificity with excellent reproducibility makes the GenoType MTBDRsl VER 2.0 a highly suitable tool for rapid screening of clinical isolates for second-line drug resistance for use in high-burden TB/HIV settings.